Measuring Psychosocial Reactions to COVID-19: The COVID Reaction Scales (COVID-RS) as a New Assessment Tool - Escolà-Gascón, Álex; Marín, Francesc-Xavier; Rusiñol, Jordi; Gallifa, Josep (Frontiers in Psychology, 2020)
Knowing and measuring the psychosocial reactions of people to the coronavirus crisis could be useful for predicting citizen responsibility and psychological well-being in the general population. In this research, we present the COVID Reaction Scales (COVID-RS), a new tool that can measure and quantify the psychopathological reactions of the population to the COVID-19 crisis. The sample consisted of 667 subjects. Explorative and confirmative factor analyses were applied to examine the validity and reliability of the COVID-RS. Five dimensions were extracted that predicted 35.08% of the variance of the psychopathological reactions: (1) disorganized behaviors, (2) avoidant behaviors, (3) maladaptive information consumption, (4) herd behaviors and (5) loneliness. The results indicated that social quarantine induces and increases psychopathological reactions. However, emotional loneliness is reduced for each person with whom the respective subject lives during the quarantine. Finally, we can conclude that the COVID-RS has satisfactory validity and reliability. Measuring dysfunctional reactions to COVID-19 can enable the prediction of citizen responsibility.